Pengaruh Kepuasan Kerja Karyawan Terhadap Komitmen Bekerja Di Industri Hotel Pada Masa Pandemi Covid-19 - Feri Ferdian; Seruni Dinitri (Politeknik Sahid, 2020)
The purpose of this study was to analyze the effect of job satisfaction on a commitment to working in the hotel industry during the Covid 19 pandemic. This type of research was conducted using a quantitative approach with ex post facto research, which is a study that aims to analyze the effect of the exogenous variable (cause), namely job satisfaction with the Endogenous variable (result), namely the commitment to work in the hotel industry during the Covid 19 pandemic. The total population in this study was 8,100,000 people consisting of all hotel employees who were sent home during the COVID-19 pandemic in Indonesia by determining the sample based on the type of purposive sampling. The data analysis technique used is simple linear regression analysis. The results showed that: (1) Employee job satisfaction at hotels during the Covid 19 pandemic was still in the abundant category. (2) the work commitment of employees at the hotel during the Covid 19 pandemic is still in a good category. (3) There is a significant influence on the job satisfaction variable on the commitment to working in the hotel industry during the Covid 19 pandemic.The magnitude of the impact of the job satisfaction variable on employee work commitment in the hotel industry during the Covid 19 pandemic is 17.4%, while 82.6% determined by other factors.